Nanosecond kinetics of multiphoton upconversion in an optically trapped single microcrystal. Issue 24 (6th June 2022) - Huang, Hanchang; Yuan, Maohui; Hu, Shuai; Zhong, Yanyi; Cui, Wenda; Guo, Chuan; Song, Changqing; Zhao, Guomin; Han, Kai
Abstract : Here, we built a setup that can optically trap single microcrystals (MCs) in solution, and determine the time-resolved multiband upconversion luminescence at a nanosecond timescale. Abstract : Recently, erbium-doped nanomaterials have been demonstrated to achieve multiband upconversion luminescence (UCL) via high excitation power and material alteration. In such a scenario, a large number of energy levels of rare-earth ions are populated, emitting light at characteristic wavelengths. However, understanding how the energy flows between these energy levels after intense excitation is rarely studied. Here, we built a setup that can optically trap single microcrystals (MCs) in solution, and record time-resolved luminescence at a nanosecond timescale. Under 976 nm nanosecond laser excitation, we observed UCL (white light) from a single β-NaYF4 :Yb/Er microcrystal (MC). Surprisingly, the Er 3+ ions are populated through four-photon upconversion (UC) processes, except for the traditional two-photon UC processes. Two populating pathways of the four-photon UC processes were observed, i.e. pathway A ( 4 I15/2 → 4 I11/2 → 4 F7/2 → 2 H11/2 → 4 S3/2 → 2 G7/2 → 4 G11/2 → 2 H9/2 → 4 F5/2 → 2 K13/2 ) and pathway B ( 4 I15/2 → 4 I11/2 → 4 I13/2 → 4 F9/2 → 2 H9/2 → 2 D5/2 ), and A was more efficient than B. Our results suggest that pathway A (which occurs first) can promote the operation of pathway B by non-radiative relaxation processes (nRPs) and back energy transfer (BET). This can provide a method to study the kinetic process of UC systems, which may facilitate the application of MCs in color displays and waveguide-based optical devices in the future.